If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 4 = 20 Reorder the terms: 2(-3 + x) + 4 = 20 (-3 * 2 + x * 2) + 4 = 20 (-6 + 2x) + 4 = 20 Reorder the terms: -6 + 4 + 2x = 20 Combine like terms: -6 + 4 = -2 -2 + 2x = 20 Solving -2 + 2x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 20 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 20 + 2 2x = 20 + 2 Combine like terms: 20 + 2 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 61/4=3/5 | | 2.5h-16=4n | | 0=(-2/3)-3 | | 1.9z+19=-19 | | f(x)=36x^2-48x-48 | | -2/5v=-14 | | 5y=2y+78 | | x^4+x^3+7x^2+9x-18=0 | | 2(x-15)x/2 | | 3x^2+22x-10=0 | | -0.65(n+8)=3.9 | | 6d^6=90 | | 5m-8n=60 | | B+5=5b+5 | | 0=-2/3-3 | | 125z=x-29 | | 6x+14=8x+20 | | 4v=2v+24 | | A/32a-7 | | 4d-8x=-18 | | 2/4=19/n | | -20/11y-19/17 | | 12.5bx+30=80 | | AD+5=B-12 | | 2x-14=3(p+5) | | 1/4(k-1)-7 | | 9/d=27/39 | | 10-3(2d-5)=6d-11 | | 10=2/3x | | 40=15-.025x | | y=-2/3x3-3 | | 5(x-5)=2(x+2)-(-4+5x) |